Fuzzy neural network IP controller for robust position control of induction motor drive - Dandil, Besir (Pergamon-Elsevier Science Ltd, 2009)
in this paper, a fuzzy neural network (FNN) controller which emulates the conventional IP controller is proposed for a vector controlled induction motor drive. A Sugeno type FNN is adopted for the proposed control system and the fuzzy neural network is so designed that the FNN controller behaves an robust-nonlinear IP controller. The proposed FNN-lP controller is used for the position control of induction motor drive and the performance and the robustness of the control system is tested for nonlinear motor loads and parameter variations. The FNN-IP controller is trained off-line using experimental data's and then the trained controller is used for experimental studies. D51104 digital signal processor control card is used to implement the control algorithm. Experimental results showing the effectiveness of the proposed control system are presented for parameter and load variations of the motor. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fuzzy neural network; IP controller; Position control; Induction motor drives